2009
DOI: 10.1021/es901991d
|View full text |Cite
|
Sign up to set email alerts
|

New Metabolites in Dibenzofuran Cometabolic Degradation by a Biphenyl-Cultivated Pseudomonas putida Strain B6-2

Abstract: A biphenyl (BP)-utilizing bacterium, designated B6-2, was isolated from soil and identified as Pseudomonas putida. BP-grown B6-2 cells were capable of transforming dibenzofuran (DBF) via a lateral dioxygenation and meta-cleavage pathway. The ring cleavage product 2-hydroxy-4-(3'-oxo-3'H-benzofuran-2'-yliden)but-2-enoic acid (HOBB) was detected as a major metabolite. B6-2 growing cells could also cometabolically degrade DBF using BP as a primary substrate. A recombinant Escherichia coli strain DH10B (pUC118bphA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
37
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 39 publications
3
37
0
1
Order By: Relevance
“…The Andrews model analyses indicated that the q max and K i of strain W1 grown on phenol were larger than that of grown on phenol + CA, which confirmed that the presence of CA or its metabolites could inhibit the growth of strain W1 and phenol degradation. Similar findings were reported for the cometabolic degradation of dibenzofuran (Li et al, 2009).…”
Section: Cometabolic Degradation Of Casupporting
confidence: 89%
See 1 more Smart Citation
“…The Andrews model analyses indicated that the q max and K i of strain W1 grown on phenol were larger than that of grown on phenol + CA, which confirmed that the presence of CA or its metabolites could inhibit the growth of strain W1 and phenol degradation. Similar findings were reported for the cometabolic degradation of dibenzofuran (Li et al, 2009).…”
Section: Cometabolic Degradation Of Casupporting
confidence: 89%
“…Several bacteria that utilize CA as the sole carbon and energy source have been isolated, and most of these bacteria have been shown to degrade CA via the angular dioxygenation and meta-cleavage pathway (Gieg et al, 1996;Schneider et al, 2000;Gai et al, 2007). Because polycyclic aromatic compounds (PACs) including CA are widespread and usually coexist in the polluted environments, cometabolic degradation of these heterocyclic compounds by bacteria growing with some others PACs should be common (Li et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Microbial remediation is one of the most effective ways to reduce these pollutants/toxicants from the environment (2,3,7,9,14). The versatile metabolic capacity of pseudomonads enables graceful degradation of these compounds (4,6,11).…”
mentioning
confidence: 99%
“…Pseudomonas putida strain B6-2 was isolated and characterized (6). With its unique tolerance to organic solvents, this superstrain can efficiently and cometabolically degrade PAHs and dioxin-like compounds, such as (polychlorinated) biphenyls, (polychlorinated) dibenzofurans, (polychlorinated) dibenzo-p-dioxins, (polybrominated) diphenyl ethers, (methylated) carbazoles, (methylated) dibenzothiophenes, and (methylated) benzothiphenes (unpublished data).…”
mentioning
confidence: 99%
See 1 more Smart Citation